Re-peasantization, Resistance and Subordination: The Struggle for Land and Agrarian Reform in Brazil - Fernandes, Bernardo Mançano [UNESP] (SAGE Publications, 2013)
The process of re-peasantization in Brazil occurs primarily through the peasant struggle for land and agrarian reform. Adopting a geographic method and using territorialization as a central axis of study, this article analyzes the history of peasant formation, particularly focusing on the formation of the Landless Rural Workers’ Movement (MST), the peasant movement that has most contributed to the process of recreating the peasantry through land occupations. The process of re-peasantization occurring over the last 30 years is supported by data showing that more than a million families have been settled through agrarian reform. However, these fractional territorial gains have not eliminated the subordination of peasants by capitalized land rent. Using data from the most recent Agricultural Census, we highlight the situation of dependence to which Brazilian peasants are submitted. The hegemony of agribusiness has provoked a reflux in the peasant struggle for land and agrarian reform, which currently finds itself stagnant. The greatest challenge for peasant movements is the creation of a development model for their territories which would enable them to recuperate the process of re-peasantization.
Keywords: agrarian reform; land struggle; Re-peasantization; resistance; subordination